Altered expression of glutamate signaling, growth factor, and glia genes in the locus coeruleus of patients with major depression - Bernard, R; Kerman, I A; Thompson, R C; Jones, E G; Bunney, W E; Barchas, J D; Schatzberg, A F; Myers, R M; Akil, H; Watson, S J (Molecular psychiatry, 2011)
Several studies have proposed that brain glutamate signaling abnormalities and glial pathology have a role in the etiology of major depressive disorder (MDD). These conclusions were primarily drawn from post-mortem studies in which forebrain brain regions were examined. The locus coeruleus (LC) is the primary source of extensive noradrenergic innervation of the forebrain and as such exerts a powerful regulatory role over cognitive and affective functions, which are dysregulated in MDD. Furthermore, altered noradrenergic neurotransmission is associated with depressive symptoms and is thought to have a role in the pathophysiology of MDD. In the present study we used laser-capture microdissection (LCM) to selectively harvest LC tissue from post-mortem brains of MDD patients, patients with bipolar disorder (BPD) and from psychiatrically normal subjects. Using microarray technology we examined global patterns of gene expression. Differential mRNA expression of select candidate genes was then interrogated using quantitative real-time PCR (qPCR) and in situ hybridization (ISH). Our findings reveal multiple signaling pathway alterations in the LC of MDD but not BPD subjects. These include glutamate signaling genes, SLC1A2, SLC1A3 and GLUL, growth factor genes FGFR3 and TrkB, and several genes exclusively expressed in astroglia. Our data extend previous findings of altered glutamate, astroglial and growth factor functions in MDD for the first time to the brainstem. These findings indicate that such alterations: (1) are unique to MDD and distinguishable from BPD, and (2) affect multiple brain regions, suggesting a whole-brain dysregulation of such functions.